Eco-innovations in the SME Sector in Recent Years – The Perspective of Selected EU Countries - Aleksandra KOSZAREK-CYRA (Communications of International Proceedings, 2021)
Pro-ecological activities are an indispensable element in achieving the goals of sustainable development. Due to the fact that SME sector enterprises are the backbone of the European economy, they play a crucial role in implementing eco-innovation. Taking such actions depends on the level of ecological awareness of decision-makers in these organizations. In this article, an attempt to evaluate pro-environmental activities in seven European Union countries - Poland, the Czech Republic, Hungary, Lithuania, Latvia, Estonia, and Slovakia was made. The conducted analyses aimed to verify the hypothesis that citizens' high environmental awareness increases the number of pro-ecological initiatives undertaken in the SME sector. The research focus was devoted to assessing changes in the number of pro-environmental activities in selected countries' SME sectors. The changes in inhibitors of these initiatives in recent years have also been analyzed. The analysis was based on data published on the European Union's Open Data Portal. The results both present the current situation and indicate the directions of activities in the future.
Keywords: Sustainable development; pro-environmental activities; eco-innovations of SMEs